Dry transfer of graphene to dielectrics and flexible substrates using polyimide as a transparent and stable intermediate layer. (17th May 2018) - Marchena, Miriam; Wagner, Frederic; Arliguie, Therese; Zhu, Bin; Johnson, Benedict; Fernández, Manuel; Chen, Tong Lai; Chang, Theresa; Lee, Robert; Pruneri, Valerio; Mazumder, Prantik
Abstract: We demonstrate the direct transfer of graphene from Cu foil to rigid and flexible substrates, such as glass and PET, using as an intermediate layer a thin film of polyimide (PI) mixed with an aminosilane (3-aminopropyltrimethoxysilane) or only PI, respectively. While the dry removal of graphene by an adhesive has been previously demonstrated—being removed from graphite by scotch tape or from a Cu foil by thick epoxy ( 20 µ m) on Si—our work is the first step towards making a substrate ready for device fabrication using the polymer-free technique. Our approach leads to an article that is transparent, thermally stable—up to 350 °C—and free of polymer residues on the device side of the graphene, which is contrary to the case of the standard wet-transfer process using PMMA. Also, in addition to previous novelty, our technique is fast and easier by using current industrial technology—a hot press and a laminator—with Cu recycling by its mechanical peel-off; it provides high interfacial stability in aqueous media and it is not restricted to a specific material—polyimide and polyamic acids can be used. All the previous reasons demonstrate a feasible process that enables device fabrication.